Examining the applicability of SPRINT in patients with subclinical or established atherothrombotic disease: A REACH registry analysis. (15th September 2017) - Varshney, Anubodh; Steg, Ph. Gabriel; Elbez, Yedid; Sorbets, Emmanuel; Eagle, Kim A.; Bhatt, Deepak L.
Abstract: Background: The optimal blood pressure (BP) target to reduce the risk of cardiovascular (CV) events remains uncertain, especially in patients with coronary artery disease (CAD). Results from the Systolic Blood Pressure Intervention Trial (SPRINT) suggest that targeting a systolic BP < 120 mm Hg decreases the rate of death and CV events in patients with hypertension and increased CV risk. We sought to evaluate the real-world applicability of SPRINT to patients with atherothrombosis. Methods: We divided 35, 411 hypertensive patients from the REACH registry into SPRINT-eligible and SPRINT-ineligible based on the trial's inclusion and exclusion criteria. We also determined the mean BP and the percentage of patients who had a systolic BP < 120 mm Hg in each group. Results: A total of 11, 993 (33.9%) patients were SPRINT-eligible, and 23, 418 (66.1%) were SPRINT-ineligible. The most common reason for SPRINT ineligibility was diabetes mellitus (64.7%). Average BP was similar in both groups (139/79 mm Hg in SPRINT-eligible patients versus 140/79 mm Hg in SPRINT-ineligible patients). A total of 10.7% of SPRINT-eligible patients and 10.6% of SPRINT-ineligible patients had a systolic BP < 120 mm Hg. Conclusions: Overall, these results indicate that in a large, global registry, most patients with atherothrombosis would not have been eligible for SPRINT and were rarely being treated to a systolic BP < 120 mm Hg. Further dedicated investigation is warranted to determine the optimal BP target in this vulnerable patient population.